한국 한센병 환자, 이중 추방된 자의 얼굴(들) - 한순미; Han Soon-mi (인문학연구, 2025)
한국 한센병[나병] 환자의 얼굴(들)은 어떻게 기억/기록되었을까. 요양소 및 병원, 사회의 안/밖에서 ‘이중 추방된 자’, 한센병 환자의 얼굴 표정과 신체는 환자, 의사, 건강한 일반인 등 시선의 위치에 따라 다르게 포착된다. 이 지점을 읽기 위해서는 여러 유형의 기록을 교차/대조하는 독법이 필요하다. 한센병 환자 작가 심숭(沈崧)의 장편소설 『애생금(哀生琴)』(1949/1950)과 치료 의사 유준(柳駿) 박사의 의학 전문서 『나병(癩病 LEPROSY)』(1962)에서는 환자의 얼굴에서 포착한 “무표정(無表情)”을 다른 맥락에서 해석한다. 심숭의 소설에서 환자 자신들이 예찬한 “그 굳세게, 씩씩하게 확충(擴充)된 얼굴빛”을 치료 전문의사는 “나병 공포증”을 야기하는 “무감각한” 표정이며 “통각(痛覺) 및 촉각의 상실”이라는 증상으로 진단한다. 이어서, 시인 한하운(韓何雲)의 자전적 수필집 『고고(孤孤)한 생명(生命)―나의 슬픈 반생기(半生記)』(1958)와 유준 박사의 『나병』(1962)에서 각각 “나병치료제”와 “나병 공포증”에 대한 서술을 대조해 본다. 시인 한하운을 비롯한 한센병 환자들의 증언, 그리고 의사 유준 박사의 저술에서는 한센병 환자의 얼굴 표정과 신체 증상, 치료제 등에 관하여 ‘매개된 시선’을 통해 이야기한다. 거기에는 한센병/환자를 바라보는 당대의 표정이 새겨 있다. 환자의 얼굴 표정과 치료의 기억을 전달하는 매개적인 시선에서 잡지 『새빛』이 주도한 계몽운동의 밑그림을 읽을 수 있다. 계몽운동기로 접어들면서 치료제의 복용과 효과, 부작용 등 의학상식의 대중화 작업이 이루어졌다. ‘제3의 의학’으로 불린 “재활” 치료가 환자와 일반인의 관심을 모았다. 그러나 여전히 한센병 환자들의 “일그러진 모습”과 “불구”의 신체가 화두였다. 향후 자료들을 보완해 읽어본다면 다른 얼굴(들)이 그려질 수 있을 것이다. How were the faces of Korean Hansen’s Disease[Leprosy] patients remembered/recorded? The facial expressions and bodies of the “double- expelled” from sanatoriums and hospitals, in/out of society, Hansen’s Disease Patients were captured differently depending on the position of the gaze. A reading method that cross-reads/contrasts diverse types of records is necessary to review these points. The full-length novel “Aaesaenggum(哀生琴)” (1949/1950) by Shimsung(沈崧), a leprosy patient and writer, and the medical book “癩病 LEPROSY” (1962) by Dr. Leprosy doctor Lew Joon(柳駿) interpreted the word “Masked Face/Expressionless(無表情)” in different contexts. The “strong, vigorous, expanded facial expression” praised by the leprosy patients in Shimsung’s novel differs from those diagnosed by the leprosy doctor. Dr. Lew Joon named the patient's facial expression the “Masked Face,” meaning that it causes “Leprophobia” and is a symptom of “loss of pain and touch.” Furthermore, this paper compares the descriptions of “Leprosy Treatment” and “Leprophobia” in poet Han Ha-un(韓何雲)’s autobiographical essay, “A Lonely Life: My Sad Half-Life Story(孤孤한 生命)” (1958) and Dr. Lew Joon’s book. In the writings of poet Han Ha-un, a leprosy patient and physician Dr. Lew Joon, they talk about the facial expressions, physical symptoms, and treatments of leprosy patients through ‘intermediate eyes.’ It contains the contemporary expressions of leprosy/patients and provides a blueprint for the Enlightenment Movement led by the magazine “The Vision” (1964-1979). As the Enlightenment Movement began, medical knowledge, including the dosage and side effects of treatment drugs for leprosy, was popularized. “Rehabilitation” treatment, called the “The Third Medicine,” attracted the attention of patients and the general public. However, The “Distorted Appearance” and “Crippled” bodies of leprosy patients were the main topics. If the subsequent studies have various data or records, other faces(s) of Korean leprosy patients may be encountered.